The Role Of Innovative Finance Mechanisms In Ict Rollout In South Africa's Education System - Mogotsi, Kelebogile (Graduate School of Business (GSB), 2024)
ICT infrastructure connectivity in South Africa is being subjected to a funding deficit, which has created a digital divide in the education sector. Despite the introduction of the SA Connect Policy by Government of South Africa, to ensure that ICT is accessible to every student in South Africa, the integration of ICT in schools occurs mostly in urban areas, and consequently, the children in rural areas are neglected or left behind. This current research, therefore, is an exploratory, qualitative study to explore the role of innovative finance mechanisms for ICT rollout in South Africa's education system. The findings of the study revealed that the current funding structure for ICT rollout in schools was ineffective. In-depth interviews were used to collect data, which were analysed, using thematic content analysis. At the conclusion of the research, it was suggested that key ICT stakeholders in South Africa should explore innovative finance mechanisms for ICT rollout, given the ineffectiveness of the current funding structure (Universal Access Fund and Universal Services and Access Obligations). The consequences of the COVID-19 pandemic, as well as the increasing use of ICT resources, and the internet, for learning purposes, clearly indicate that the role of innovative finance needs to be considered, to achieve SDG 4: “inclusive and equitable quality education and promote lifelong learning opportunities for all.”